ОСОБЛИВОСТІ ВПЛИВУ СПІВПРАЦІ МІЖ РАДОЮ ЄВРОПИ ТА ЄВРОПЕЙСЬКИМ СОЮЗОМ НА РОЗВИТОК СУЧАСНОГО МІЖНАРОДНОГО ПРАВА - Viktor Nalutsyshyn; Volodymyr Burdin; Marta Mochulska; Vitalii Chornenkyi; Halyna Owerko (IAEME Publication, 2020)
The intensification of cooperation between the Council of Europe (CoE) and the European Union (EU) is of considerable interest to Ukraine, which has identified entry into the European legal space as one of the key vectors of its development. The study is devoted to the study of the peculiarities of the impact of cooperation between the Council of Europe and the European Union on the development of modern international law. The authors explored the evolution of formation and development of cooperation between the CoE and the EU; highlighted the legal aspects of cooperation between the CoE and the EU in the process of EU enlargement; to find out the peculiarities of the impact of cooperation between the CoE and the EU on the development of modern international law and to characterise the international legal forms of cooperation between the CoE and the EU.
FEATURES OF THE IMPACT OF COOPERATION BETWEEN THE COUNCIL OF EUROPE AND THE EUROPEAN UNION ON THE DEVELOPMENT OF MODERN INTERNATIONAL LAW
Keywords: Cooperation; Council of Europe (CoE); Development; the European Union (EU); International Intergovernmental Organization (IIO); International Law